Peran Teknologi AI PAUDPEDIA sebagai Media Pembelajaran Interaktif dalam Meningkatkan Literasi Digital Anak Usia Dini di TK ABA 3 Samarinda - Sari, Padia Nadila; Salehudin, Mohammad (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
In the contemporary era, digital literacy is a crucial skill, particularly in early childhood education (PAUD). It encompasses not just the ability to utilize technology but also the skills to disseminate information, communicate effectively, and collaborate within a digital context. A notable innovation in PAUD learning support is the use of artificial intelligence (AI)-based media, such as PAUDPEDIA. This platform is tailored to offer adaptive content, instant feedback, and an engaging, enjoyable learning experience. The aims of this research is to evaluate the implication of PAUDPEDIA as an interactive educational tool in enhancing digital literacy among early learners at TK ABA. Therefore, developing the competence of educators in utilizing technology such as PAUDPEDIA is a strategic step to support quality education in the digital era.